Жанрові вияви інтенцій регламентування в офіційно-діловому дискурсі - Шабат-Савка, Світлана; Shabat-Savka, Svitlana (Східноєвропейський національний університет імені Лесі Українки, 2015)
У статті розглянуто офіційно-діловий дискурс як мовленнєвий жанр, визначено його інтенційну домінанту; схарактеризовано інтенції, експліковані в документах законодавчого характеру, у царині міждержавних дипломатичних стосунків, в адміністративно-канцелярській сфері; проаналізовано систему мовних засобів, що увиразнюють комунікативні інтенції регламентування в текстах офіційно-ділового стилю. The article presents the study of the official business discourse as communicatively unilateral genre of communication in public-political, legal and social and economic life of the society, defining its intentional dominant – intention of regulation which has a distinct antropooriented and imperative character. Status and role differentiation of the officially-business discourse is the basis for highlighting three genre manifestations of intentions of regulation. Specifically, the article describes intentions explicated in legal documents, and intentions in the field of diplomatic relations; the system of discursive-marked means of placing emphasis on a particular intention (declarative utterances, stereotyped expressions, incentive constructions, performatives, I-statements and constructs of speech etiquette).
Genre-Specific Manifestations of Intentions of Regulation in Official Business Discourse.
Keywords: комунікативна інтенція; мовець; офіційно-діловий дискурс; жанр; стиль; синтаксичні конструкції; communicative intention; speaker; official business discourse; genre; style; syntactic constructions